Fabrication of silver nanostructures using femtosecond laser-induced photoreduction. (23rd November 2017) - Barton, Peter; Mukherjee, Sanjoy; Prabha, Jithin; Boudouris, Bryan W; Pan, Liang; Xu, Xianfan
Abstract: Silver nanostructures were fabricated by femtosecond laser-induced reduction of silver ions and the impact of solution chemistry on the fabricated structures was evaluated. By investigating the exact photochemistry of the nanofabrication solutions, which contained varying amounts of diamine silver ions, trisodium citrate, and n-lauroylsarcosine sodium, and optimizing the laser processing parameters, we fabricated two-dimensional silver pads with surface roughness values of 7 nm and stable 2.5-dimensional shell structures with heights up to 10 μ m and aspect ratios of 20 in a ready manner. Moreover, thermal annealing of these structures afforded materials where the average resistivity value was only a factor of 4 greater than that of bulk silver. In this way, the work presented here provides for a methodology that can be used for laser direct fabrication of metal nanostructures for applications in plasmonics and micro- and nano-electronics.